Synthesis and Crystal Structure of Ni(II) Complex with 3-Hydroxyadamantane-1-carboxylic Acid and 4,4’-Bipyridine - Hu, Xiao-Chun; Zhao, Guo-Liang; Liu, Jian-Feng; Bian, Yu-Yan; Kong, Li-Chun (Asian Journal of Chemistry, 2010)
A novel dinickel(II) complex [Ni2(HOC10H14COO)4(H2O)(4,4'-bipy)2]·7H2O (1), consisting of monodentate and bidentate coordinated 3-hydroxyadamantane-1-carboxylic acid (HOC10H14COO–) ligand, 4,4'-bipyridine (4,4'-bipy) and water molecules, has been synthesized under hydrothermal conditions and characterized by FTIR spectrum, thermogravimetric analysis and single-crystal X-ray diffraction. It crystallizes in the monoclinic system, space group Pc with a = 1.1995(3) nm, b = 2.0489(4) nm, c = 1.7595(3) nm, b = 132.978(10) °, V = 3.1637(11) nm3, Z = 2, Mr = 1354.80 F(000) = 1440, Dc = 1.422 g cm-3, μ(MoKa) = 0.674 mm-1, the final R = 0.0614 and wR = 0.1012 for 4245 observed reflections (I > 2s(I)). The structure reveals that the complex forms a robust twofold interpenetrated diamond structure net. CCDC: 720487.